2020
DOI: 10.1007/s13346-020-00733-4
|View full text |Cite|
|
Sign up to set email alerts
|

Atorvastatin-loaded solid lipid nanoparticles as eye drops: proposed treatment option for age-related macular degeneration (AMD)

Abstract: Statins, widely prescribed for cardiovascular diseases, are also being eyed for management of age-related macular degeneration (AMD). Poor bioavailability and blood-aqueous barrier may however limit significant ocular concentration of statins following oral administration. We for the first time propose and investigate local application of atorvastatin (ATS; representative statin) loaded into solid lipid nanoparticles (SLNs), as self-administrable eye drops. Insolubility, instability, and high molecular weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 112 publications
2
44
0
1
Order By: Relevance
“…The presented research on lipid-based nanocarriers has also shown that one optimisation problem can be approached following different experimental designs, still arriving, in any case, at valid polynomials [97]. For instance, the same formulation problem regarding solid lipid nanoparticles has been optimised by a three-level full factorial, central composite, Box-Behnken or Taguchi designs [120,125,134,155]. It is important to underline that one single experimental design will in most cases not offer all the responses and that meticulous planification and statistical analysis are more important than experimental work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presented research on lipid-based nanocarriers has also shown that one optimisation problem can be approached following different experimental designs, still arriving, in any case, at valid polynomials [97]. For instance, the same formulation problem regarding solid lipid nanoparticles has been optimised by a three-level full factorial, central composite, Box-Behnken or Taguchi designs [120,125,134,155]. It is important to underline that one single experimental design will in most cases not offer all the responses and that meticulous planification and statistical analysis are more important than experimental work.…”
Section: Discussionmentioning
confidence: 99%
“…Several examples of CCDs applied to lipid nanoparticle optimisation found in the literature are reported in Table 3 . Particularly, Yadav and colleagues [ 125 ] recently proposed a new approach for the treatment of age-related macular degeneration based on atorvastatin-loaded solid lipid nanoparticles intended to be topically administered. Preliminary studies allowed them to demonstrate that the concentration of all the four formulation components (lipid matrices and co-/surfactants) affected the responses under study.…”
Section: Optimising the Outcomes: Statistical Design Of Experiments (Doe)mentioning
confidence: 99%
“…SLNs were investigated in a potential self-administrable eye drop formulation for the management of age-related macular degeneration. They were found to increase bioavailability in aqueous and vitreous humor and to be more stable than free atorvastatin [ 54 ]. On the other hand, hot HPH has its limitations, which include temperature-induced drug degradation and drug loss to the aqueous phase during homogenization [ 55 ].…”
Section: Methods For Slns and Nlcs Preparationmentioning
confidence: 99%
“…Nano-sized drug delivery systems may become useful in enhancing the therapeutic potential of statins [ 202 , 203 ]. Just recently, Yadav et al investigated for the first time the effects of topically applied atorvastatin (ATS; representative statin) loaded into solid lipid nanoparticles as self-administrable eye drops [ 204 ]. The authors proposed that topical application of statins as eye drops will achieve high ocular concentration resulting in a consistent therapeutic effect [ 204 ].…”
Section: Therapy Strategies In Amd Targeting the Vasculature And Omentioning
confidence: 99%